2021
DOI: 10.31004/edukatif.v3i6.1472
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Modul Kimia Dasar Berbasis Discovery Learning pada Materi Stoikiometri

Abstract: Selain model pembelajaran, salah satu bahan ajar yang dapat digunakan dalam menunjang keberhasilan proses pembelajaran adalah modul Modul disebut juga media untuk belajar mandiri karena di dalamnya telah dilengkapi petunjuk untuk belajar sendiri Adapun tujuan penelitian ini adalah untuk mengetahui pengembangan modul kimia dasar berbasis discovery learning pada materi stoikiometri yang valid, mengetahui pengaruh hasil belajar mahasiswa terhadap bahan ajar yang telah dikembangkan dan kelayakan modul kimia dasar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…The second factor is that the developed medium is consistent with the content and learning objectives. One of the aspects contributing to the success of media development is the compatibility between media and learning objectives and materials, because learning media is a tool that teachers can use to facilitate the learning process (Andriani et al, 2019;Hasanah et al, 2021 ;Simangunsong & Pane, 2021). In teaching and learning activities, media serve as a conduit between the teacher and students for the delivery of content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second factor is that the developed medium is consistent with the content and learning objectives. One of the aspects contributing to the success of media development is the compatibility between media and learning objectives and materials, because learning media is a tool that teachers can use to facilitate the learning process (Andriani et al, 2019;Hasanah et al, 2021 ;Simangunsong & Pane, 2021). In teaching and learning activities, media serve as a conduit between the teacher and students for the delivery of content.…”
Section: Discussionmentioning
confidence: 99%
“…Using learning modules to facilitate the learning process is one method for overcoming these obstacles. Modules are independent, dispersed, and non-group-study-oriented instructional resources (Andriani et al, 2019;Hasanah et al, 2021;Simangunsong & Pane, 2021). Modules typically feature material, methodologies, limitations, and evaluation techniques that are structured in a logical and appealing manner to attain the desired outcomes (Gazali & Ningsih, 2019;Roziyah & Kamaludin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because chemical content is abstract, students frequently struggle to understand it (A. D. B. Simangunsong & Pane, 2021). So far, textbooks have merely filled students with concepts that must be memorized, rather than inviting students to think as a process of developing their knowledge and experience to identify concepts that must be grasped by themselves, as well as their meaning and relevance to life (A. D. Simangunsong, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the chemistry is abstract, students frequently struggle to grasp it (A. D. B. Simangunsong & Pane, 2021). These challenges might result in students having a poor comprehension of many chemical topics.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the average students' achievement increased from 54,14 to 75,43 and the mastering learning of student increased from 47,14% to 88,57%. Simangunson and Pane (2021) used research and development to produce discovery learning chemistry module for stoichiometry topic. The module produced was feasible, practical, and effective to be used in chemistry learning an well as increased basic chemistry learning outcome of students.…”
Section: Introductionmentioning
confidence: 99%